Cerebral Venous Thrombosis Presenting As Subarachnoid Hemorrhage: Clinical Case - Agbotsou, Komi Igneza; Tanoh Amon, Muriel Tchwa; Theuriet, Julian Paul Theodore; Debras, Corinne; Albanesi, Carlo; Philippeau, Frederic (European Scientific Journal, ESJ, 2021)
Subarachnoid hemorrhage is typically due to an aneurysmal rupture. Cerebral venous thrombosis is a rare cause, especially if the clinical presentation is atypical. We report a patient with unusual acute headaches, with an entirely normal physical examination. His cerebral MRI, and cerebral venous angio-MRI documented a cerebral venous thrombosis associated with subarachnoid hemorrhage. The outcome was favorable with anticoagulant treatment.